Recente "køkkenmøddinger" i Ghana - Noe-Nygaard, Nanna (Geografisk Tidsskrift, 1967)
DK: Afhandlingen er både i en dansk og en engelsk version. Figurerer og referencer optræder kun i den danske version, men der er figurtekster på både dansk og engelsk. ENG: This article is both available in a Danish and an English version. The figures and references only appear in the Danish version, but the captions are in both Danish and English. English title: Present-day "kitchen middens" in Ghana